Aggregate idiosyncratic volatility and stock return predictability: Evidence from the Korean stock market. Issue 4 (2nd October 2017) - Kim, Jungmu; Lee, Changjun
ABSTRACT: Employing various proxies of idiosyncratic volatility, we investigate the relationship between aggregate idiosyncratic volatility and future market returns in Korea. We find a positive association between aggregate idiosyncratic volatility and subsequent market returns, and especially, that the idiosyncratic volatility measure proposed by Garcia, Mantilla-García, and Martellini (2014) has a striking forecasting power for future market excess returns. The predictive power of aggregate idiosyncratic volatility is robust to several considerations including weighting schemes, market variance and trading exchanges. Overall, our empirical results indicate that aggregate idiosyncratic volatility plays an important role in predicting future stock returns in the Korean stock market.